The Effect of Fermentation Duration on the NPK Content and C/N Ratio in Chicken Manure Using M21 - Rizky Hidayah Siregar; Kurniawan Sinaga (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aimed to determine the effect of fermentation time on nitrogen (N), phosphorus (P), potassium (K) contents, and the C/N ratio of chicken manure with the addition of the M21 bioactivator. The experiment employed several fermentation-duration treatments analyzed through laboratory testing, and the data were evaluated using analysis of variance (ANOVA). The results showed that the average nitrogen content in each treatment was P0 = 0.698%, P1 = 1.114%, P2 = 1.164%, and P3 = 1.144%. Fermentation time had no significant effect (P>0.05) on phosphorus (P) content but had a significant effect (P0.05) at each week of observation, although numerically it decreased from P0 to P3. This decrease in the C/N ratio indicates an improved decomposition process of organic matter during fermentation. Therefore, it can be concluded that fermentation duration affects the C/N ratio as well as N and K contents but does not influence the P content of chicken manure compost. The best quality compost was obtained in treatment P2 with 21 days of fermentation, showing N content of 1.164%, P of 1.032%, and K of 1.322%. Overall, the C/N ratio values in fermented treatments (P1–P3) met the Indonesian National Standard SNI 7763:2018, indicating their potential use as environmentally friendly organic fertilizer